MEMAHAMI STRATEGI, TANTANGAN, DAN SOLUSI PENGINTEGRASIAN LITERASI DIGITAL DALAM KURIKULUM INKLUSIF UNTUK SDGs 2030 - Dita Sri Wahyuni; Karisma, Nabila Andra Mutia; Ichsan Fauzi Rachman (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Education is an instrument in shaping students' personalities so that they become a quality and inclusive generation. One of the essential strategies that can be implemented to realize the 2030 Sustainable Development Goals (SDGs) is by integrating digital literacy in an inclusive curriculum. This research aims to understand effective and efficient teaching strategies in an inclusive curriculum, identify challenges and solutions faced in integrating digital literacy, and explore the effectiveness of implementing digital literacy into an inclusive curriculum in increasing students' understanding and skills in the context of the 2030 SDGs. Using the method literature review, this research collects and analyzes data from various literature sources related to integrating digital literacy in an inclusive curriculum. The results of this research show that integrating digital literacy requires a holistic and adaptive approach, involving various educational stakeholders to overcome technological, curriculum and human resource barriers. Apart from that, this research also found that implementing teaching strategies that utilize digital technology can significantly improve students' skills and understanding so that it will support the achievement of SDGs 2030. The implications of these findings are expected to help curriculum developers and educational practitioners in designing and implementing teaching practices more effectively and inclusive. Keywords: digital, curriculum, literacy